Reconsidering the role of online tutors in asynchronous online discussions - Vlachopoulos, Panos (Proceedings of the International Conference on Networked Learning, 2008)
A number of publications in the field of e-learning highlight the importance of the “moderator’s” approach to developing students’ online learning. They identify that the major challenges for online teachers arise from the diversity of roles which moderators are required to undertake. However, little is reported about the roles e-moderators actually adopt in different learning contexts, and how these range between ‘teaching’ and ‘facilitating’. This research focused on the ways in which several different e-moderators in higher education approached the online learning with students. Four case studies were carried out in two research settings of blended learning, which involved fully online sessions. The first three case studies, as part of the first research setting, offered an insight into the moderation practices of a novice moderator and two guest expert moderators and the reaction of seventeen students to these moderation practices. The fourth one explored in a different research setting the moderation of a group of twenty five students by a moderator, who was the face-to-face lecturer of the same group of students. A grounded theory approach was used to analyse and interpret the data. This generated a comparative insight into diverse moderation practices, and the consequent actions and reactions of e-moderators and students. The study found that there were pre-established relationships between the various actors involved in the discussions, which directly influenced how moderators intervened, and how students reacted. Distinct differences were identified in the ways individual moderators decided when and how to intervene. This resulted in a learner or teacher centred approach with a concentration on process or content. One of the main aspects of the moderation practice was therefore identified as ‘the dichotomy of moderation’, which is discussed in this paper.